(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2014)
This work was carried out on a branch of the mangrove swamp Wildlife Reserve Manglares El Salado, that is located adjacent to the third bridge off the Perimetral road. In order to evaluate the availability of individuals of Nodilittorina varia on the rocky-muddy substrate, the mathematical Poisson distribution model was applied. Thus, plots of 30 cm2 were sampled in an area of 800 m2, randomly distributed randomly throughout, the individuals were recorded during low tides. The research showed up that the mathematical method of Poisson in Nodilittorina varia at random distribution was not entirely satisfactory, since it was found that the studied species presented rather a provision of aggregated or contagious character. This was checked by Chi-Square test for Goodness Fit, with significant differences.